Extraction of hops pelletized (Humulus lupulus) with subcritical CO2 and hydrodistillation: Chemical composition identification, kinetic model, and evaluation of antioxidant and antimicrobial activity. (May 2023) - Fischer, Bruno; Gevinski, Eduardo Vinicios; da Silva, Diego Maroso; Júnior, Paulo Amaurí Lando; Bandiera, Valmor José; Lohmann, Andreia Menin; Rigo, Diane; Duarte, Patrícia Fonseca; Franceschi, Elton; Zandoná, Giovana Paula; Rombaldi, Cesar Valmor; Cansian, Rogério Luis; et al.
Graphical abstract: Highlights: Hydrodistillation and subcritical CO2 extraction influence the chemical composition. Different extraction yields were obtained from the four hop varieties. Hydrodistillation obtained sesquiterpenes hydrocarbons as the main constituents. Subcritical CO2 extraction presents oxygenated and non-oxygenated sesquiterpenes. Abstract: Hop essential oil and hop extract using carbon dioxide (CO2 ) are products with high added value because they have bioactive and sensory properties. In this context, the objective of this study was to obtain and characterize essential oil and extracts from pelleted hops of El Dorado, Polaris, Hallertau Blanc and Callista varieties using hydrodistillation and subcritical CO2 extraction methods. Extraction yield ranged from 0.38 % to 1.97 % (m/m) for essential oils and from 8.76 % to 15.35 % (m/m) for extracts using subcritical CO2 . The chemical compositions of the essential oils were mainly monoterpene (18.14 % to 29.91 %) and sesquiterpene (46.01 % to 59.03 %) hydrocarbons and for the extracts were sesquiterpene hydrocarbons (33.05 % to 71.90 %) and oxygenated sesquiterpenes (14.80 % to 34.89 %). The extracts showed better antioxidant activity than essential oils due to the presence of phenolic compounds and flavonoids. Hop extracts showed some antimicrobial activity, but essential oils did not demonstrate antimicrobial potential. Hop extracts obtained with subCO2 have the potential to be used in the brewing industry as a flavoring and as natural antioxidants.